Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Kelokopi Batusangkar - Andrika Aldi; Violintikha Harmawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The purpose of this study was to find out how service quality affects customer happiness at Kelokopi Batusangkar, which was shown by comments about unsteady Wi-Fi connections, uneven drink tastes, and slow service from staff who didn't know the menu. What the study aims to do is show how service quality affects customer happiness. A non-probability picking method was used to select 370 people for the study, which used a detailed quantitative approach and a cause correlation method. A Likert-scale questionnaire that had been checked for validity and reliability was used to collect data, and SPSS 24.00 was used to analyze the results.The findings showed that 83% of people were satisfied with the service quality and 78% were satisfied with the service quality. Only 31.2% of customer happiness was caused by service quality; the other 69.8% was caused by other things.